2005
DOI: 10.1017/s1041610205001018
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the scientific evidence for the efficacy of a palliative care approach in advanced dementia

Abstract: Background:Patients with dementia often receive poor end-of-life care, with inadequate pain control and without access to the palliative care services that patients with cancer are offered. This has been identified as an area of need in recent U.K. Government reports and by the Alzheimer's Society (U.K.). Our objective was to perform a systematic review of the scientific literature regarding the efficacy of a palliative care model in patients with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
138
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(142 citation statements)
references
References 5 publications
1
138
1
2
Order By: Relevance
“…Undertreatment of symptoms is a frequently-cited concern in dementia at the end of life [29,59], but few studies verify this concern with untreated pain infrequently reported [47,60,61]. An Italian study reported that over three-quarters of patients in pain were treated pharmacologically [37].…”
Section: Symptoms and Treatment At The End Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…Undertreatment of symptoms is a frequently-cited concern in dementia at the end of life [29,59], but few studies verify this concern with untreated pain infrequently reported [47,60,61]. An Italian study reported that over three-quarters of patients in pain were treated pharmacologically [37].…”
Section: Symptoms and Treatment At The End Of Lifementioning
confidence: 99%
“…Overtreatment with burdensome interventions is another widely reported phenomenon [29,59] although this varies across nations. Antibiotics were used in over 40% of US, UK, Swiss, and Italian patients dying with dementia [28,37,41,47,[63][64][65].…”
Section: Symptoms and Treatment At The End Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…91 It has been identified that people with dementia, for example, rarely gain access to palliative or supportive care, 92 contrary to evidence that points to the efficacy of such an approach for people with this condition. 93 Several reviews point unequivocally to the importance of adopting palliative approaches in the case of non-malignant diseases such as dementia, particularly in acute settings. [94][95][96] There is also continuing evidence of inequalities in referral to and use of specialist palliative care services for older people.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, over half of people with dementia die in a nursing home . Reviews of evidence to date have drawn heavily on evidence from settings where there is access to medical and specialist palliative care services for this population (Coventry et al, 2005;Hughes et al, 2005;Robinson et al, 2005;Sampson et al, 2005;Zwakhalen et al, 2006;Birch and Draper, 2008). Generalist palliative care frameworks may increase awareness of the issues for people with dementia.…”
Section: Introductionmentioning
confidence: 99%